Two exceptionally stable luminescent MOFs for the selective and sensitive detection of Fe3+ ions in aqueous solution. Issue 40 (27th September 2019) - Deng, Liming; Zhang, Yaowen; Zhang, Dan; Jiao, Shaoshao; Xu, Jixiang; Liu, Kang; Wang, Lei
Abstract : Two exceptionally stable MOFs were selected as highly efficient sensors for the rapid, sensitive and selective detection of Fe 3+ in aqueous solution. Abstract : Both an excess and shortage of iron(iii ), away from normal permissible limits, can induce serious disorders, therefore its detection is significant, but still remains a challenge. Luminescent metal–organic frameworks (LMOFs) are a class of attractive materials for the detection of Fe 3+ ions. However, improvement in their hydrolytic stability, speed, sensitivity, and selectivity of function is the key to the advanced application of LMOFs in an aqueous environment. Herein, two hydrostable LMOFs, Zn-DTA and Cd-DTA, based on the π-conjugated aromatic ligand 2, 5-di(1 H -imidazol-1-yl)terephthalic acid (H2 DTA), were selected as highly efficient sensors for the rapid, sensitive and selective detection of Fe 3+ in aqueous solutions. On the basis of the rigid structure and multiple coordination sites of the H2 DTA ligand, Zn-DTA and Cd-DTA possess brilliant stability and excellent fluorescence emission. Both of them exhibit high selectivity ( K sv = 8400 and 6420 M −1 ) and high sensitivity (0.82 and 1.07 μM) for the rapid detection (less than 30 s) of small quantities of Fe 3+ (0.2 mg mL −1 ) in water. It is worth noting that the compounds not only remain stable in the water for a long time but also maintain structural integrity at high temperatures. To the best of our knowledge, Zn-DTA and Cd-DTA, as two exceptionally stable MOF chemosensors used for the selective detection of Fe 3+, show very rare behavior compared to the reported Zn/Cd-MOFs. The quenching mechanism for such a high selectivity can be mainly explained by the competition between the absorption of Fe 3+ and the excitation of the compounds. Moreover, the introduced carboxyl O atoms of Zn-DTA additionally donate their lone-pair electrons to the Fe 3+ ions, leading to enhanced detection ability. Our work reveals the enormous potential of LMOFs as an appealing platform upon which to construct sensing materials.